1981
DOI: 10.1161/01.hyp.3.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral renal function responses to converting enzyme inhibitor (SQ 20,881) in two-kidney, one clip Goldblatt hypertensive rats.

Abstract: SUMMARYThe influence of the renln-angiotensin system on individual kidney function of two-kidney, one clip Goldblatt hypertensive (GH) rats was evaluated by determining renal functional responses during intravenous infusion of converting enzyme inhibitor (CEI) (SQ 20,881, 0 J rag/100 g-hr) for 3.5 bourn. Rats were made hypertensive by placing a 0.25 mm silver clip on the right renal artery 3-4 weeks prior to study. Normal rats and GH rats were prepared to allow urine collections from each kidney. Mean arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 34 publications
5
49
1
Order By: Relevance
“…Increased Miyauchi et al, 1989;Criscione et al, 1990), decreased (Dohi & Luscher, 1990b;Auch-Schwelk & Vanhoutte, 1989) and normal responses (Diederich et al, 1989;Criscione et al, 1990) to endothelin-1 have been reported in vessels from spontaneously hypertensive rats. The responsiveness of resistance arteries to endothelin-1 in renovascular hypertension would be of pathophysiological interest, since this type of hypertension is characterized by an increased activity of the renin-angiotensin system (Brunner et al, 1962;Fourcade et al, 1971;Ploth et al, 1977;Huang et al, 1981;Miyazaki et al, 1986;Wilson et al, 1989) and because angiotensin II stimulates the production of endothelin in cultured endothelial cells (Emori et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Increased Miyauchi et al, 1989;Criscione et al, 1990), decreased (Dohi & Luscher, 1990b;Auch-Schwelk & Vanhoutte, 1989) and normal responses (Diederich et al, 1989;Criscione et al, 1990) to endothelin-1 have been reported in vessels from spontaneously hypertensive rats. The responsiveness of resistance arteries to endothelin-1 in renovascular hypertension would be of pathophysiological interest, since this type of hypertension is characterized by an increased activity of the renin-angiotensin system (Brunner et al, 1962;Fourcade et al, 1971;Ploth et al, 1977;Huang et al, 1981;Miyazaki et al, 1986;Wilson et al, 1989) and because angiotensin II stimulates the production of endothelin in cultured endothelial cells (Emori et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…This responsiveness of the non-clipped kidney to blockade of the reninangiotensin system persists even during the maintenance phase of hypertension when the plasma renin and ANG II concentrations have returned to near normal levels (36,38). The continued influence of ANG II on the non-clipped kidney after circulating levels return towards normal is of critical importance to the hypertensinogenic process (31,33,37,47,49,50).…”
Section: Responses To Unilateral Renal Arterial Stenosismentioning
confidence: 99%
“…In the 2K1C model of renovascular hypertension, hypertension is induced by unilateral stenosis of the renal artery, usually by application of a silver clip. In general, the stenosis is not so severe to cause ischemia and the normal autoregulatory mechanism helps maintain renal blood flow and GFR near normal levels (33). However, the reduced renal perfusion pressure stimulates renin release from the stenotic kidney.…”
Section: Responses To Unilateral Renal Arterial Stenosismentioning
confidence: 99%
See 2 more Smart Citations